Plasma levels of the lymphangiogenic factors VEGF-C, VEGF-D, and CXCL-12 are elevated in advanced diabetic nephropathy - Qingshan Tian; Fan Zhang; Zhichao Yang; Ji Miao; Hao Wu; Zhenzhong Zheng (Renal Failure)
Objective Early biomarkers for diabetic nephropathy progression remain limited. This study aims to investigate whether plasma levels of VEGF-C, VEGF-D, and CXCL-12 can reflect the severity of diabetic kidney disease (DKD), and to evaluate their potential as biomarkers for disease monitoring.Methods Patients were divided into normal albuminuria group (UmAlb < 30 mg/24 h, n = 30), microalbuminuria group (UmAlb 30–300 mg/24 h, n = 30) and macroalbuminuria group (UmAlb >300 mg/24 h, n = 30). Healthy individuals were included as control group (n = 30). Plasma levels of vascular endothelial growth factor-C (VEGF-C), vascular endothelial growth factor-D (VEGF-D), and chemokine ligand 12 (CXCL-12) were measured.Results The plasma levels of VEGF-C, VEGF-D, and CXCL-12 were significantly increased in all type 2 diabetic kidney disease groups. Correlation analysis revealed that plasma VEGF-C, VEGF-D and CXCL-12 levels were positively correlated with plasma creatinine and urinary microalbumin. Furthermore, these levels were inversely correlated with estimated glomerular filtration rate. In order to distinguish DKD patients in the normal albuminuria group, microalbuminuria group, and macroalbuminuria group, the areas under the receiver operating characteristic curve (AUC-ROCs) of VEGF-C was 0.668 (95%CI: 0.531–0.805), 0.790 (95%CI: 0.678–0.901), and 0.850 (95%CI: 0.756–0.944), respectively. For VEGF-D, the AUC-ROCs were 0.718 (95%CI: 0.587–0.848), 0.873 (95%CI: 0.783–0.963), and 0.931 (95%CI: 0.872–0.991), respectively. Finally, for CXCL-12, the AUC-ROCs were 0.687 (95%CI: 0.554–0.820), 0.816 (95%CI: 0.710–0.921), and 0.903 (95%CI: 0.829–0.977), respectively.Conclusion Plasma VEGF-C, VEGF-D, and CXCL-12 levels is of great value for early diagnosis and assessment of diabetic kidney disease severity. This suggests that these may serve as valuable surrogate markers for clinical outcomes in DKD.